2012
DOI: 10.1017/s0025315412001440
|View full text |Cite
|
Sign up to set email alerts
|

Benthic foraminifera assemblages in turtle congregation sites along the north-east coast of India

Abstract: Near-shore recent benthic foraminifera from three ecologically important (Olive Ridley turtle congregation sites) but vulnerable sites encompassing 23 sampling stations (12 in Rushikulya, 5 in Devi and 6 in Gahirmatha) along coastal Orissa, north-west Bay of Bengal (BoB) in India were studied for the first time for their composition, distribution and assemblage patterns. Thirty-nine species of benthic foraminifers (from 6 orders and 23 families) were identified of which all 39 were present in Rushikulya, 22 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…These findings on the abundance and assemblage patterns of meiofauna are in agreement with previous studies in the area of Rushikulya (e.g. Bhattacharjee et al, 2013).…”
Section: R E S U L T S a N D Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings on the abundance and assemblage patterns of meiofauna are in agreement with previous studies in the area of Rushikulya (e.g. Bhattacharjee et al, 2013).…”
Section: R E S U L T S a N D Discussionsupporting
confidence: 93%
“…Bhattacharjee et al, 2013), free living nematodes were collected and examined. Interestingly, two suctorian ciliates were observed as epibionts on the cuticles of one free living marine nematode, Chromaspirina sp.…”
Section: Introductionmentioning
confidence: 99%
“…This is perhaps surprising since lagoon assemblages must be viable over a greater range of environmental conditions than those found subtidally in brackish water habitats, and suggests that despite their isolated nature, dispersal opportunities remain sufficient to maintain the input of estuarine/marine species. Bhattacherjee et al (2013) reported benthic foraminiferal assemblages along coastal Orissa. Thirty-nine species (belonging to 6 order and 23 families) of Foraminifera were collected from three coastal areas viz.…”
Section: Resultsmentioning
confidence: 99%
“…As they have a short life span (from a few days up to one year, Murray, 1991;Nigam et al, 2003;Kurtarkar et al, 2019), they respond to small changes in the environment. Due to these characteristics, foraminifera is extensively used as a tool for monitoring the coastal environment along with different marginal environments like estuarine (Alve, 1995;Bhattacharjee et al, 2013;Luan & Debenay, 2005), marsh (Gehrels & Newman, 2004;Horton & Murray, 2007) and lagoonal environment (Martins et al, 2013;Samir, 2000).…”
Section: Introductionmentioning
confidence: 99%